Beliefs and factors influencing teachers’ deployment of social media in instructional delivery in public basic schools in a developing and low-tech country - Ama Otwiwah Adu-Marfo; Moses Kumi Asamoah; Abigail A. Aryeh-Adjei; Janice Miller -Young (Social Sciences and Humanities Open)
Elaborate and detailed policies like the Accelerated Development Policy, ICT in Education Policy, and the new Standard-based Curriculum have significantly advanced technology integration in Ghanaian schools. However, integrating digital technologies like social media into public basic school curricula remains a challenge, unlike in tertiary education. This study employed a qualitative multi-case study, using semi-structured interviews and focus group discussions to investigate teachers' beliefs and factors influencing their use of social media tools for teaching. Twenty-four teachers were selected using homogeneous and convenience sampling techniques, adhering to research ethics and data quality principles. Thematic analysis revealed that teachers' beliefs about the importance, helpfulness, and competence of using social media tools significantly influenced their integration into teaching. Nevertheless, inadequate ICT infrastructure and lack of school leadership direction hindered social media deployment. To address these challenges, we recommend that the government develop and enforce technology-based teaching policies at basic schools and provide regular training programs for teachers and school administrators to enhance their capacity for effective ICT-based education implementation.